A Case of Palytoxin Poisoning in a Home Aquarium Enthusiast and His Family. (26th October 2015) - Hall, Christine; Levy, David; Sattler, Steven
Abstract : Inhalational exposure to palytoxin is an extremely rare cause of respiratory distress. This little-known marine toxin has the potential to cause significant morbidity and mortality. Toxicity has been best documented in cases of ingestion but has also been seen in cases of dermal exposure and inhalation of vapors. Palytoxin has been found in several coral species, some of which are favored by home aquarium enthusiasts and are commercially available. We report a case of a family who were exposed to the aerosolized toxin following the cleaning of a coral in their home aquarium. It is important that clinicians be aware of this source of toxic exposure to provide necessary care to these patients.